Principles of physics - Bueche, Frederick J.; Jerde, David A. (Massachusetts : McGraw Hill Education, 1995)
This text presents a one-year, introductory, laboratory-based course in physics at the college algebra and elementary trigonometry.
Part One. Mechanics -- Part Two. Mechanical and thermal properties of matter: oscillations and waves -- Part Three. Electricity and magnetism -- Part Four. Light and optics.
Includes bibliographical references and index.
Keywords: PHYSICS